Stability result of higher-order fractional neutral stochastic differential system with infinite delay driven by Poisson jumps and Rosenblatt process. Issue 2 (3rd March 2020) - Dhanalakshmi, K.; Balasubramaniam, P.
Abstract: In this manuscript, we establish the stability results of higher-order fractional neutral stochastic differential system (FNSDs) with infinite delay driven by Poisson jumps and Rosenblatt process via the Nussbaum fixed point theorem. The results are obtained by a new integral inequality. The validation of the efficiency of the proposed method is done through a numerical example.